PARTISIPASI CIVIL SOCIETY DALAM MENGEMBANGKAN PARIWISATA DI KABUPTEN LAMPUNG SELATAN (STUDI PADA KELOMPOK SADAR WISATA DI KABUPATEN LAMPUNG SELATAN) - Department, administratio; Dewi, Wulan Kusuma; Hermawan, Dedy (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. Public participation in the public policy process is one of the principles of Good Governanceby involving one actor of the civil society, the Tourism Awareness Group (Pokdarwis) which is inaccordance with the Good Governance principles in which society is not only as a policy object but as asubject. This study aims to analyze and describe the reinforcement of Pokdarwis involvement indeveloping tourism an identifying the supporting and inhibiting factors of Pokdarwis in developingtourism in South Lampung Regency. This study used a qualitative approach with data collectiontechniques done by means of interview, observation and documentation. The results and discussionshowed that the Tourism Awareness Group involvement in developing tourism is not carried outthoroughly by Pokdarwis in South Lampung Regency. There are 2 groups in Penengah Subdistrict andRajabasa Subdistrict which have been involved in the planning stage to the utilization stage. However,two subdistricts of Bakauheni and Kalianda participated till the planning stage only. The supportingfactors, included: supports from stakeholders and the government; while the inhibiting factors,included: lack of awareness from Pokdarwis, the limited fund and other problems. Keywords: Participation, Civil Society, and Tourism